(untitled) (Journal of Economic Research & Business Administration, 2021)
The digital economy is increasingly replacing the everyday economy. The continued rapid pace of technology development and its use in business presents exciting opportunities for entrepreneurs and challenges for tax authorities. In the digital economy, traditional correspondences, dependencies, and proportions inherent in the industrial-market economy are no longer effective. Traditional methods of regulation in the new economy are no longer effective, especially in the field of taxation. We need new tax rules that take into account the specifics of the technologies used. The rules should reflect the use of virtual currencies, digital goods, classification and taxation principles. The purpose of the study is to identify the main problems in the taxation of the digital economy and ways to solve them based on foreign experience. The scientific significance of the research is based on the study of the theory and practice of taxation in the field of digital economy. The practical significance of the research is justified by the possibility of using the research materials for further assessment and solution of taxation problems in the digital economy. The research in the article was carried out on the basis of information from international and public organizations, scientific works of foreign scientists. Such research methods as analysis, analogy, abstraction and concretization were used. Key words: digital economy, taxation, cryptocurrency, transfer pricing, the “arm’s length” principle.